Population structure and diversity of common bean (Phaseolus vulgaris L.) landraces in the Peruvian Amazon - Jorge Tobaru; Marvin Barrera-Lozano; Carlos D. Vecco-Giove; Jorge Peláez; Mack Pinchi; Yesenia Vargas; Jorge Chuquillanqui; Julian Soto-Torres; Ronald Robles; David Saravia; Cesar Petroli; Jorge D. Etchevers; et al. (PLoS ONE, 2026)
Common bean ( Phaseolus vulgaris L.) is a globally important grain legume, yet the genetic diversity of landraces from the Peruvian Amazon remains poorly characterized. This study aimed to assess the population structure and genetic diversity of Amazonian common bean by integrating morphological and genome-wide SNP data. A total of 476 accessions were phenotyped using 18 morphological traits, and 647 accessions were genotyped with 23,050 high-quality DArTseq SNP markers. Cluster and population structure analyses consistently identified two major genetic groups corresponding to the Andean (n = 284) and Mesoamerican (n = 363) gene pools, with further subdivision into four subgroups at K = 4. Principal Coordinate Analysis supported this structure, with the first axis explaining 62.62% of the variation in the molecular data. Genetic diversity was high, with 94.9% of SNPs successfully mapped and more than 94% of loci polymorphic in both groups. However, observed heterozygosity was low (Ho = 0.035–0.041) compared to expected heterozygosity (He ≈ 0.147–0.148), and inbreeding coefficients were high (FIS = 0.52–0.54), consistent with the predominantly self-pollinating mating system. Hill number analyses indicated similar allelic richness between groups (q = 0: α ≈ 1.95–1.97) and low differentiation in allele presence (β = 1.04), whereas differentiation increased when allele frequencies were considered (q = 2: β ≈ 1.4–1.5). Morphological analyses revealed substantial phenotypic variation, including flowering time (32–75 days), pod length (6.5–17.3 cm), and number of locules per pod (2–11), and identified four distinct phenotypic clusters. No redundant accessions were detected. These results indicate that Amazonian landraces harbor high levels of genetic and phenotypic diversity structured by gene pool origin and local adaptation. The integration of morphological and SNP data provides a robust framework for germplasm characterization and highlights the importance of conserving these genetic resources for future breeding and sustainable agriculture.